Notes on the conventual economy: The Monastery of Santa Clara del Cusco - Burns, Kathryn (1991)
The first religious institutions in Peru dedicated themselves not only to winning the hearts and minds of the Andean people, but to displacing their religion, taking control of their ritual centers and earthly resources. Thus we have, in the center of the ancient empire, the monastery of Santo Domingo above the maximum temple of Coricancha, in an architectural "manifesto" very typical of the time.